(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2021)
An report of the creative process of the Santa Catarina group Eranos Círculo de Arte in a home environment during the pandemic, through the construction of puppets and creation of short scenes. Rod Puppets with a structure printed in 3d were developed based on the work of Hansjürgen Fettig, which gave rise to the short scenes Am(ar), Coração Inbox, A Tempestade and Jornaleco. The impossibility of a face-to-face meeting with the audience drastically altered the group's theatrical production.